Criteria of talent in sports - Hohmann, A.; Dierks, B.; Luehnenschloss, D.; Seidel, I.; Wichmann, E. (2001)
The search, diagnosis and promotion of talents is in many sports disciplines one of the most important tasks of training science. On one side the scientific approaches of the research on talent are focussed on the heredity and developmental stability of different endogenious anatomical and physiological components, that effect future success in sport. On the other side these studies are added by investigations, which analyse the influence of contextual variables on the long term development of sport performance. Such exogenious variables are e. g. the support systems in the environment of the ath-letes and the quantity and quality of training load. In this concept of talent research two transitions from a narrow to a wide approach and from a static to a dynamic approach took place (see figure 1). In our study on the development of performance in sports talents we investigated the swimmers of the Elite Sports School in Magdeburg/Germany.